Ciências Da Saúde 4 2019
DOI: 10.22533/at.ed.2991915027
|View full text |Cite
|
Sign up to set email alerts
|

Função Mastigatória, Movimentos Mandibulares E Atividade Elétrica Do Músculo Masseter Em Crianças E Adolescentes Respiradores Oronasais

Abstract: Boca -Doenças. 2. Higiene bucal. 3. Saúde bucal. I. Cardoso, Nayara Araújo. II. Rocha, Renan Rhonalty. III. Série. CDD 614.4 Elaborado por Maurício Amormino Júnior -CRB6/2422 O conteúdo dos artigos e seus dados em sua forma, correção e confiabilidade são de responsabilidade exclusiva dos autores. 2019 Permitido o download da obra e o compartilhamento desde que sejam atribuídos créditos aos autores, mas sem a possibilidade de alterá-la de nenhuma forma ou utilizá-la para fins comerciais. www.atenaeditora.com.br… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
1

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
0
1
Order By: Relevance
“…The present study found a mean of 12.13 for the mandibular mobility variable in oronasal, differing from another study 25 , which also used AMOFE in oronasal, which found an average of 14.00 for the same variable.…”
Section: Discussioncontrasting
confidence: 99%
“…The present study found a mean of 12.13 for the mandibular mobility variable in oronasal, differing from another study 25 , which also used AMOFE in oronasal, which found an average of 14.00 for the same variable.…”
Section: Discussioncontrasting
confidence: 99%